Capitalisme politique et développement dépendant en Asie du Sud-Est - François Bafoil (Revue de la Régulation)
Many features characterize the laggards of developing States: a specific form of political authority based on clan domination; concessions policies; poor diversification of the economic structures; the importance of the foreign funds and a widespread corruption. The ‘Special Economic Zones’ in Cambodia and Laos mirror such constraints at the local level. Drawing on very advantageous fiscal measures for foreign investors and deregulated social rules, they become more and more numerous. Due to a lack of efficient public institutions, the dissemination of growth is weak around these zones and economic and social development is missing. These different components are at the basis of the concept of political capitalism.